2019
DOI: 10.1007/978-3-030-32692-0_23
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Rodent Brain MRI Lesion Segmentation with Fully Convolutional Networks

Abstract: Manual segmentation of rodent brain lesions from magnetic resonance images (MRIs) is an arduous, time-consuming and subjective task that is highly important in pre-clinical research. Several automatic methods have been developed for different human brain MRI segmentation, but little research has targeted automatic rodent lesion segmentation. The existing tools for performing automatic lesion segmentation in rodents are constrained by strict assumptions about the data. Deep learning has been successfully used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Our fully-automatic approach is trained end to end, requires no preprocessing, and it was validated on a large and diverse data set composed by 916 MRI rat brain scans at nine different lesion stages from 671 rats utilized to study focal cerebral ischemia. We extend our earlier conference paper (Valverde et al, 2019 ) by (1) improving our previous ConvNet (Valverde et al, 2019 ) with a deeper and different architecture and providing an ablation study (Meyes et al, 2019 ) justifying certain architectural choices; (2) evaluating the generalization capability of our model on a considerably larger and more heterogeneous data set via Dice coefficient, compactness and Hausdorff distance under different training settings (training set size and different ground truth); and (3) making RatLesNetv2 publicly available.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our fully-automatic approach is trained end to end, requires no preprocessing, and it was validated on a large and diverse data set composed by 916 MRI rat brain scans at nine different lesion stages from 671 rats utilized to study focal cerebral ischemia. We extend our earlier conference paper (Valverde et al, 2019 ) by (1) improving our previous ConvNet (Valverde et al, 2019 ) with a deeper and different architecture and providing an ablation study (Meyes et al, 2019 ) justifying certain architectural choices; (2) evaluating the generalization capability of our model on a considerably larger and more heterogeneous data set via Dice coefficient, compactness and Hausdorff distance under different training settings (training set size and different ground truth); and (3) making RatLesNetv2 publicly available.…”
Section: Introductionmentioning
confidence: 56%
“…Manual segmentation can be prohibitively time-consuming as studies involving animals may acquire hundreds of three-dimensional (3D) images. Furthermore, the difficulty of defining lesion boundaries leads to moderate inter- and intra-rater agreement; previous studies have reported that Dice coefficients (Dice, 1945 ) between annotations made by two humans can be as low as 0.73 (Valverde et al, 2019 ) or 0.79 (Mulder et al, 2017a ). Moderate inter-rater agreement is caused by several factors that affect the segmentation quality, including partial volume effect, image contrast and annotator's knowledge and experience.…”
Section: Introductionmentioning
confidence: 99%
“…This architecture has been shown to generalize even from a limited amount of annotated data [25], and as such is well suited for medical imaging, where datasets as large as the ones commonly used for CNNs are rare. Valverde et al [26] recently demonstrated the effectiveness of U-Net-like architectures in preclinical research, designing the first DNN for the segmentation of ischemic lesions in rodents and achieving segmentation accuracy comparable or better to inter-rater agreement in manual segmentation.…”
mentioning
confidence: 99%
“…Some CNN-based networks without pre- or post-processing had been proposed for automatic segmentation of brain lesions on MR images ( 22 , 23 ). However, a pre-processing was still conducted in the present study to normalize all the slices and discard the slices without white matter, gray matter and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%
“…The contours of WML and AIL manually delineated by the observers were considered as the gold standard. Subsequently, a rating scheme from 0 to 9 was used to evaluate the WML burden of each individual (21) (Figure 1). Table 2 exhibits the distributions of the WML rating scores in training and testing sets.…”
Section: Gold Standardmentioning
confidence: 99%